A method for predicting mechanical properties of a multi-laser powder bed fusion formed Ti-6Al-4V alloy
By calculating the inherent strength, grain boundary strengthening, and dislocation contribution of the material, the yield strength of Ti-6Al-4V alloy formed by multi-laser powder bed melting is predicted, which solves the problems of inaccuracy and low efficiency in the prediction of mechanical properties in the prior art, and realizes efficient prediction and optimization of mechanical properties.
Patent Information
- Application Number
- CN202610981291.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-02
- Publication Date
- 2026-11-06
AI Technical Summary
Existing technologies for multi-laser powder bed melting and forming of Ti-6Al-4V alloys cannot accurately predict mechanical properties. They mainly rely on the traditional "black box" trial-and-error method, which lacks universality and ignores microstructure characteristics, resulting in high experimental costs, low efficiency, and inability to adapt to changes in component size or equipment.
By calculating the material's inherent strength, grain boundary strengthening, and dislocation contribution, and based on Hall-Petch strengthening theory and Taylor hardening model, the yield strength of multi-laser powder bed fused Ti-6Al-4V alloy is predicted, taking into account the influence of microstructure.
This technology enables efficient and accurate prediction of the mechanical properties of Ti-6Al-4V alloys formed by multi-laser powder bed melting, reduces experimental cycles, and promotes the optimized application of large-size components, especially in the aerospace and defense industries.
Smart Images

Figure CN123053288A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of additive manufacturing technology, and in particular relates to a method for predicting the mechanical properties of Ti-6Al-4V alloy formed by multi-laser powder bed melting. Background Technology
[0002] Ti-6Al-4V alloy holds an irreplaceable position in high-end equipment manufacturing fields such as aerospace and medical devices due to its high specific strength, excellent corrosion resistance, and good biocompatibility. In recent years, laser powder bed fusion, as a highly representative additive manufacturing technology, has broken through the geometric limitations of traditional subtractive manufacturing. However, with the increasing demand from industry for integrated, large-size, complex components, traditional single-laser powder bed fusion systems have encountered bottlenecks in forming efficiency and processing size. Multi-laser powder bed fusion technology has emerged to address this, significantly improving printing efficiency through multi-laser collaborative scanning and becoming a core development direction in the current additive manufacturing field. Although multi-laser technology significantly improves manufacturing efficiency, it introduces the highly challenging problem of "multi-laser overlap." Figure 1 and 2 As shown, in the multi-laser powder bed melting process, the alternating action of different laser beams causes the material to undergo a more complex and intense non-equilibrium thermal cycle than that of a single laser. This complex thermal history behavior results in microstructural differences in the Ti-6Al-4V alloy between the multi-laser overlap region and the single-laser independent region, such as α-phase, β-grain size and fine-grain structure, which in turn affects the macroscopic mechanical properties of the formed sample.
[0003] Currently, the optimization of the mechanical properties of Ti-6Al-4V alloys formed by multi-laser powder bed melting mainly relies on the traditional "black box" trial-and-error method of "process parameters - macroscopic properties". This method not only consumes a lot of time and has high experimental costs, but also heavily depends on experience and lacks universality. Once the component size or equipment changes, the original process window often becomes invalid. In addition, most existing numerical simulations are limited to the prediction of macroscopic temperature or stress fields, ignoring the "microscopic structural characteristics" that determine the material's essential mechanical behavior, and thus failing to accurately reveal the microscopic physical mechanisms of material deformation and fracture. Summary of the Invention
[0004] In view of this, the present invention provides a method for predicting the mechanical properties of Ti-6Al-4V alloy formed by multi-laser powder bed melting. The method predicts the yield strength of Ti-6Al-4V alloy based on microstructure, which is used to reveal the response relationship between microstructure evolution and macroscopic mechanical properties under complex thermal history of multi-laser melting.
[0005] This invention predicts the yield strength of an alloy by calculating three parameters: the inherent strength of the material, grain boundary strengthening, and dislocation strengthening. The inherent strength of the material is the strength of the alloy under ideal conditions, i.e., in a single-crystal state, contributed by the lattice friction of the elements themselves. For alloying elements, element doping affects the atomic distribution of the main element, i.e., the base element, leading to lattice deformation. This element doping can be classified as strong pinning or weak pinning effects, thus contributing to solid solution strengthening. The lattice shear force of the base element and the element pinning effect provide the inherent strength of the alloy. However, in reality, materials are often polycrystalline, and the rapid solidification of additive manufacturing leads to a large accumulation of dislocations within the formed sample. Therefore, when predicting the strength of actual formed samples, the contribution of friction between grain boundaries (Hall-Petch strengthening) and the deformation resistance provided by dislocation density (Talyor hardening) must also be considered. Therefore, the yield strength prediction of this invention is calculated based on the inherent strength of the material, the contribution of Hall-Petch strengthening, and the contribution of Talyor hardening.
[0006] To achieve the above objectives, the technical solution of the present invention is as follows: A method for predicting the mechanical properties of Ti-6Al-4V alloy formed by multi-laser powder bed melting includes the following steps: Determine the inherent strength: Based on the composition of the Ti-6Al-4V alloy, determine the base elements and strengthening elements of the alloy, and calculate the inherent strength σ0 of the Ti-6Al-4V alloy; Determining the grain boundary strengthening contribution intensity: Based on the phase composition, grain size, and proportion of the Ti-6Al-4V alloy, the intensity σ of the grain boundary strengthening contribution in the single-laser region and the multi-laser overlapping region was calculated using the Hall-Petch strengthening theory. H-P ; Determining the dislocation contribution intensity: Based on the dislocation density of the Ti-6Al-4V alloy, the intensity σ of the dislocation contribution in the single-laser region and the multi-laser overlap region was calculated using the Taylor hardening model. Taylor ; Predicting mechanical properties: based on yield strength σ y =σ0+σ H-P +σ Taylor The yield strength of the single-laser region and the multi-laser overlapping region were calculated respectively.
[0007] Preferably, the inherent strength σ0 includes the lattice stress σ of the substrate element. CRSS Solid solution strengthening of elements σ SS ,
[0008] In the Ti-6Al-4V alloy, Ti is the base element, and Al and V are the strengthening elements. Based on the random distribution of Al and V atoms, it belongs to the Labusch weak pinning model; therefore, the elemental solid solution strengthening σ SS for:
[0009] Where i represents elements Al and V, K is the solid solution strengthening coefficient of the element, and c is the atomic volume fraction.
[0010] Preferably, based on characterization methods, it is known that the Ti-6Al-4V alloy has α-phase, β-phase, and fine-grained structural regions at the initial β-phase grain boundaries, as well as their respective proportions. The strength of the grain boundary strengthening contribution is then obtained based on Hall-Petch strengthening theory.
[0011] Where f is the fine grain area fraction, d is the grain size, and k is the Hall-Petch strengthening factor.
[0012] Preferably, the grain size and the area ratio of different phases in the single-laser region and the multi-laser overlap region are obtained by OM, SEM, EBSD or TEM characterization.
[0013] Preferably, the k of the α phase α =114 MPa·μm 1 / 2 β phase k β =600 MPa·μm 1 / 2 k, the fine-grained structure region at the initial β-phase grain boundary fine =114 MPa·μm 1 / 2 .
[0014] Preferably, the dislocation density of the Ti-6Al-4V alloy is obtained through characterization methods, and the intensity of dislocation strengthening contribution in the single-laser region and the multi-laser overlap region is obtained according to the Taylor hardening model:
[0015] Where M is the Taylor factor, with a value of 2.8; α is the dislocation action constant, with a value of 0.5; G is the shear modulus, with a value of 44 GPa; b is the Burger vector, with a value of 0.3 nm; and ρ is the dislocation density.
[0016] Preferably, the dislocation density in the single-laser region and the multi-laser overlap region is characterized and analyzed by EBSD.
[0017] Because the present invention adopts the above technical solution, it has the following advantages and positive effects compared with the prior art: This invention calculates the inherent strength of a metallic alloy, then, based on the microstructure, tests the phase composition and grain size, and uses Hall-Petch strengthening theory to obtain the strength contributed by grain boundary strengthening. Finally, by testing the dislocation density of the alloy at the microstructure level, the dislocation contribution strength is calculated, thereby obtaining the mechanical properties of the formed specimen. Specifically, this application differs from conventional Hall-Petch strengthening calculations by comprehensively considering the combined influence of the proportion of each phase in the multi-laser powder bed melting formed Ti-6Al-4V alloy, calculating the contribution of grain boundary strengthening and the inherent strength of the alloy, calculating the dislocation contribution strength based on the Taylor hardening mechanism, and finally predicting the yield strength of the formed specimen through the linear superposition of multiple strengthening mechanisms. Attached Figure Description
[0018] Figure 1 The microstructure of a single laser-melted Ti-6Al-4V sample characterized by optical microscopy according to an embodiment of the present invention; Figure 2 The microstructure of the multi-laser melt-formed Ti-6Al-4V sample characterized by optical microscopy according to an embodiment of the present invention; Figure 3 The microstructure of the Ti-6Al-4V sample formed by single-laser powder bed melting, as characterized by EBSD in this embodiment of the invention; Figure 4 This is a comparison diagram of the predicted mechanical structure and the experimental structure of the Ti-6Al-4V alloy sample in an embodiment of the present invention. Detailed Implementation
[0019] To avoid the traditional "black box" trial-and-error method that relies on "process parameters - macroscopic performance," this invention proposes a method based on microstructure prediction of the mechanical properties of Ti-6Al-4V alloys formed by multi-laser powder bed melting. This method can assist in predicting the mechanical properties of large-size Ti-6Al-4V components formed by multi-laser powder bed melting, thereby adjusting forming process parameters and optimizing the mechanical properties of the Ti-6Al-4V alloy. This promotes the practical application of multi-laser powder bed melting Ti-6Al-4V alloy components in key fields such as aerospace and defense. This method significantly reduces experimental cycles.
[0020] The following detailed description, in conjunction with the accompanying drawings and specific embodiments, provides a method for predicting the mechanical properties of Ti-6Al-4V alloy formed by multi-laser powder bed melting, as proposed in this invention. The advantages and features of this invention will become clearer from the following description.
[0021] The Ti-6Al-4V alloy used in this embodiment is a commercially available alloy powder, composed of nearly 90% Ti, 6.08% Al, and 4.06% V by mass. The alloy was formed into Ti-6Al-4V samples by multi-laser powder bed melting.
[0022] 1. Determine the inherent strength of the material The base element of the Ti-6Al-4V alloy sample was determined to be Ti, providing a fundamental strength equivalent to the lattice friction stress of pure Ti, approximately 180 MPa. Al and V are the stabilizing elements of the α and β phases, respectively, i.e., strengthening elements. The random distribution of Al and V strengthening elements is attributed to the Labusch weak pinning model. Therefore, the inherent strength of the Ti-6Al-4V alloy can be determined by the lattice friction stress σ of the base element. CRSS Solid solution strengthening of elements σ SS Calculation yielded:
[0023] Among them, elemental solid solution strengthening is calculated based on the Labusch weak pinning model:
[0024] Where i represents elements Al and V, K is the solid solution strengthening coefficient of the element, and c is the atomic volume fraction. The corresponding volume fraction is calculated based on the mass fractions of Al and V, and K is obtained by consulting [the relevant database]. Al = 285 MPa·at. -2 / 3 and K V = 879 MPa·at. -2 / 3 Calculate elemental solid solution strengthening σ SS The strength is approximately 128 MPa, therefore, the inherent strength of the alloy is approximately 308 MPa.
[0025] 2. Determine the grain boundary strengthening contribution intensity: The thermal history of the laser overlap region in multi-laser powder bed fusion molding samples differs from that of the single-laser independent region, thus leading to differences in the molten pool morphology and regional microstructure, such as... Figure 1 and Figure 2 As shown, variations in grain size and dislocation density affect the mechanical properties of the formed specimen; therefore, the combined effects of the α-axis, β-phase, and fine-grained structure proportions need to be considered. Thus, the grain boundary strengthening contribution intensity is:
[0026] Where f is the fine grain area fraction, d is the grain size, and k is the Hall-Petch strengthening coefficient. The value of k is determined based on the microstructure characteristics; for the α phase, k... α The value range is generally from 114 to 516 MPa·μm. 1 / 2 The pressure was set to 114 MPa·μm based on a grain size of less than 250 nm. 1 / 2 For the β phase, k β The value range is generally 500 to 700 MPa·μm 1 / 2Set to 600 MPa·μm 1 / 2 Furthermore, considering the fine-grained structure distributed at the initial β grain boundaries, its intensity contribution in this region is calculated separately. fine Value and k α Consistent, also set to 114 MPa·μm 1 / 2 .
[0027] The EBSD characterization results showed that the α-phase grain sizes of the single-laser and dual-laser lap-formed samples were 82.2 μm and 100.7 μm, respectively, and the β-phase grain sizes were 0.23 μm and 0.19 μm, respectively. The EBSD characterization results for the single-laser powder bed fusion formed Ti-6Al-4V sample are as follows: Figure 3 As shown. TEM characterization results showed that the grain sizes of the fine-grained structures in the single-laser region and the double-laser overlap region were approximately 0.06 μm and 0.07 μm, respectively, and the fine-grained area fractions f in the single-laser region and the double-laser overlap region were 0.11 and 0.14, respectively. Therefore, the grain boundary strengthening contributions of the α-direction, β-phase, and fine-grained structure in the single-laser region were calculated to be 211.6 MPa, 66.2 MPa, and 51.2 MPa, respectively, and the grain boundary strengthening contributions of the α-direction, β-phase, and fine-grained structure in the double-laser overlap region were 224.9 MPa, 59.8 MPa, and 60.3 MPa, respectively.
[0028] 3. Determine the dislocation contribution intensity: The strength of the dislocation contribution was calculated using the Taylor hardening model:
[0029] Where M is the Taylor factor, with a value of 2.8; α is the dislocation interaction constant, with a value of 0.5; G is the shear modulus, with a value of 44 GPa; b is the Burger vector, with a value of 0.3 nm; and ρ is the dislocation density. The dislocation densities of the Ti-6Al-4V samples in the single-laser region and the double-laser overlap region, measured by EBSD characterization, were 6.18 × 10⁻⁶ and 6.18 × 10⁻⁶, respectively. 14 / m 2 and 6.60×10 14 / m 2 Therefore, the dislocation contribution intensities in the single-laser region and the dual-laser overlap region are calculated to be 459.4 MPa and 474.8 MPa, respectively.
[0030] 4. Predicting the mechanical properties of molded specimens Based on the strength contributions of different strengthening mechanisms calculated in steps 1 to 3, the predicted yield strength is calculated:
[0031] The yield strength values of the single-laser region and the double-laser overlap region of the alloy sample were calculated to be 1096.4 MPa and 1127.8 MPa, respectively.
[0032] 5. Verify the effectiveness of mechanical properties. Tensile tests were performed on the single-laser region and the double-laser overlap region of the alloy sample. The yield strengths of the single-laser region and the double-laser overlap region were measured to be 1122.3±15.5MPa and 1170.0±15.3MPa, respectively.
[0033] Comparing the predicted mechanical structure of the Ti-6Al-4V alloy sample with the experimental structure, for example... Figure 4 As shown, this demonstrates the effectiveness of the method provided by the present invention for predicting the mechanical properties of Ti-6Al-4V alloys based on microstructure in multi-laser powder bed melting.
[0034] The embodiments of the present invention have been described in detail above with reference to the accompanying drawings, but the present invention is not limited to the above embodiments. Even if various changes are made to the present invention, if these changes fall within the scope of the claims of the present invention and their equivalents, they shall still fall within the protection scope of the present invention.
Claims
1. A method for predicting the mechanical properties of Ti-6Al-4V alloy formed by multi-laser powder bed melting, characterized in that, Includes the following steps: Determine the inherent strength: Based on the composition of the Ti-6Al-4V alloy, determine the base elements and strengthening elements of the alloy, and calculate the inherent strength σ0 of the Ti-6Al-4V alloy; Determining the grain boundary strengthening contribution intensity: Based on the phase composition, grain size, and proportion of the Ti-6Al-4V alloy, the intensity σ of the grain boundary strengthening contribution in the single-laser region and the multi-laser overlapping region was calculated using the Hall-Petch strengthening theory. H-P ; Determining the dislocation contribution intensity: Based on the dislocation density of the Ti-6Al-4V alloy, the intensity σ of the dislocation contribution in the single-laser region and the multi-laser overlap region was calculated using the Taylor hardening model. Taylor ; Predicting mechanical properties: based on yield strength σ y =σ0+σ H-P +σ Taylor The yield strength of the single-laser region and the multi-laser overlapping region were calculated respectively.
2. The method for predicting the mechanical properties of Ti-6Al-4V alloy formed by multi-laser powder bed melting according to claim 1, characterized in that, The inherent strength σ0 includes the lattice stress σ of the substrate element. CRSS Solid solution strengthening of elements σ SS , In the Ti-6Al-4V alloy, Ti is the base element, and Al and V are the strengthening elements. Based on the random distribution of Al and V atoms, it belongs to the Labusch weak pinning model; therefore, the elemental solid solution strengthening σ SS for: Where i represents elements Al and V, K is the solid solution strengthening coefficient of the element, and c is the atomic fraction.
3. The method for predicting the mechanical properties of Ti-6Al-4V alloy formed by multi-laser powder bed melting according to claim 1, characterized in that, Characterization methods revealed that the Ti-6Al-4V alloy possesses α-phase, β-phase, and fine-grained structural regions at the initial β-phase grain boundaries, along with their respective proportions. Based on Hall-Petch strengthening theory, the intensity of grain boundary strengthening contribution was obtained: Where f is the fine grain area fraction, d is the grain size, and k is the Hall-Petch strengthening factor.
4. The method for predicting the mechanical properties of Ti-6Al-4V alloy formed by multi-laser powder bed melting according to claim 3, characterized in that, The grain size and the area ratio of different phases in the single-laser region and the multi-laser overlap region were obtained by OM, SEM, EBSD or TEM characterization.
5. The method for predicting the mechanical properties of Ti-6Al-4V alloy formed by multi-laser powder bed melting according to claim 3, characterized in that, k of α phase α =114 MPa·μm 1 / 2 β phase k β =600 MPa·μm 1 / 2 k, the fine-grained structure region at the initial β-phase grain boundary fine =114 MPa·μm 1 / 2 .
6. The method for predicting the mechanical properties of Ti-6Al-4V alloy formed by multi-laser powder bed melting according to claim 1, characterized in that, The dislocation density of the Ti-6Al-4V alloy was determined using characterization methods, and the intensity of dislocation strengthening contributions in the single-laser region and the multi-laser overlap region was obtained based on the Taylor hardening model. Where M is the Taylor factor, with a value of 2.8; α is the dislocation action constant, with a value of 0.5; G is the shear modulus, with a value of 44 GPa; b is the Burger vector, with a value of 0.3 nm; and ρ is the dislocation density.
7. The method for predicting the mechanical properties of Ti-6Al-4V alloy formed by multi-laser powder bed melting according to claim 6, characterized in that, Dislocation densities in single-laser regions and multi-laser overlap regions were characterized and analyzed using EBSD.
